2018
DOI: 10.1007/978-3-030-05931-6_18
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Mode Impedance Controlled Smart Fingered Microgripper for Automated Grasp and Release Tasks at the Microscale

Abstract: The grasp and release of objects have been widely studied in robotics. At the microscale, this problem becomes more difficult due to the microscale specificities which are notably manifested by the high dynamics of microsystems, their small inertia, their fragility, the predominance of surface forces and the high complexity of integrating adapted sensors.In this paper, the problem of the grasp/release task is considered at the microscale. A new nonlinear controller design based on Sliding Mode Impedance Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Adam et al [10] also highlighted the importance to consider force sensors and robots together when doing microrobotic based force sensing while Govillas et al [11] shown the strong influence of angular imperfections during compression tests. Specific strategies can also be investigated based on accurate force and or position dynamic measurement to succeed in achieving complex tasks at the microscale [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Adam et al [10] also highlighted the importance to consider force sensors and robots together when doing microrobotic based force sensing while Govillas et al [11] shown the strong influence of angular imperfections during compression tests. Specific strategies can also be investigated based on accurate force and or position dynamic measurement to succeed in achieving complex tasks at the microscale [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This capability has been demonstrated as a key interest for the manipulation of biological objects as well as for manufactured microstructures [ 19 ]. Moreover, such force sensing enables implementing original robotic strategies that strengthen flexible decision making against an unknown environment [ 20 ].…”
Section: Introductionmentioning
confidence: 99%